(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Seaweeds have bioactive compounds of interest in the pharmaceutical industry. In India, seaweeds are used exclusively for phycocolloids production and have not yet received consideration as a dietary supplement. So, it has become imperative to explore the biomedical potential of seaweeds and promote their utilization as a functional food. The seaweeds Turbinaria ornata, Gracillaria crassa and Laurencia papillosa, collected from the Tuticorin coast of the Southeast coast of India and selected based on preliminary screening, were extracted with acetone and evaluated for antiulcer, wound healing and hepatoprotective activities. L. papillosa showed the highest level of gastric protection activity (81%) at 200 mg/kg, comparable to the standard drug ranitidine (90%). G. crassa followed with 76%. G. crassa and L. papillosa, showed marked wound-healing activity. G. crassa at 200 mg/kg, showed a marked effect on the serum marker enzymes indicating prominent hepatoprotective activity. The noteworthy wound-healing and hepato-protective properties of G. crassa besides anti-ulcer activity next to L. papillosa were indicative of its potential for further consideration.